Valoración de empresas: en busca del precio justo - Narváez Liceras, Alejandro (2009)
More than once professional and academic people from the business world have noted than the Business valuation is in most of the cases, an art to manage numbers with the intention of some established objectives. No doubt, there is something certain in this phrase, but to do this we need a deep knowledge of the related difficulties and problems to assign the real value to an on going company. The objective of this article is to examine different aspects of business valuation through the use of future outputs. We will explain some of the reasons why we chose this method and we will mention the way we quantify the related variables.